2022
DOI: 10.1039/d1gc04270j
|View full text |Cite
|
Sign up to set email alerts
|

Comparative life cycle and economic assessments of various value-added chemicals' production via electrochemical CO2 reduction

Abstract: Herein, life cycle and economic assessments are conducted to evaluate the energy impacts, environmental impacts, and economic benefits of various value-added chemicals' (C1- and C2-) production via electrochemical CO2 reduction based on flow cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…[ 10,11 ] Specifically, the requirement of a good CO 2 RR catalyst is to maintain high current density at low overpotential, with high selectivity and durability. [ 12,13 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10,11 ] Specifically, the requirement of a good CO 2 RR catalyst is to maintain high current density at low overpotential, with high selectivity and durability. [ 12,13 ]…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Specifically, the requirement of a good CO 2 RR catalyst is to maintain high current density at low overpotential, with high selectivity and durability. [12,13] Metalloporphyrin (MN 4 -Por, Figure 1a), with unique metal-N 4 (MN 4 ) units as active sites, has been demonstrated as effective homogeneous catalyst for CO 2 RR. [14][15][16][17][18][19][20][21][22][23] However, the large-scale application of such materials has been limited due to low current density and difficult recovery.…”
mentioning
confidence: 99%
“…This not only helps to reduce CO 2 emissions but may also create new economic opportunities. [7][8][9] However, it is important that these transformations are as efficient as possible, requiring a minimal energy input and producing minimal waste. To achieve this goal, researchers must adopt the principles of green chemistry and engineering, [10] which emphasize the design of chemical processes that are inherently safe, efficient, and sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, chemists and chemical engineers have an important role to play in developing new synthetic methodologies that can capture and use CO 2 and convert it into added‐value compounds. This not only helps to reduce CO 2 emissions but may also create new economic opportunities [7–9] …”
Section: Introductionmentioning
confidence: 99%
“…Techno-economic analysis (TEA) has demonstrated that the cost of electricity and selectivity of products are key to determining the economics of eCO 2 RR products. Unfortunately, most assessments simplify the product separation process using only the cost of ordinary distillation for the liquid-phase products, ignoring the fact that the separation scheme will be different for different products. Therefore, which kind of separation strategy and how to reduce the energy consumption should be considered. Furthermore, despite the rapid growth of industrial CO 2 electrolysis technology, whether this process truly yields negative CO 2 emissions remains a puzzle.…”
mentioning
confidence: 99%